USE OF ELECTRONIC EDUCATIONAL RESOURCES IN LEARNING A FOREIGN LANGUAGE IN UNIVERSITY - Musaev, Uralova, Abduvali, Nigora (Журнал иностранных языков и лингвистики, 2021)
This article is about using electronic educational resources in learning foreign languages in universities. It analyzes efficiency of application of innovative technologies in the formation of foreign language professional competence of students.